ZnO nanoparticle-grafted PLA thermoplastic composites for 3D printing applications: Tuning of thermal, mechanical, morphological and shape memory effect. (June 2022) - Kumar, Ranvijay; Singh, Rupinder; Singh, Mohit; Kumar, Pawan
The zinc oxide (ZnO)-grafted polymers have emerged as a prominent material for fabrication of 3D printed biosensor due to its inherent antibacterial, antifungal, room temperature ferromagnetic magnetic behaviour, crystallinity, high thermal conductivity and high exaction binding energy. In this study, ZnO (nanoparticles (NPs)) were grafted with polylactic acid (PLA) using twin-screw compounder for preparations of feedstock filaments. The filaments were prepared by varying input parameters of twin-screw compounder such as ZnO concentration in PLA (0–2%), forced loading (10–15 kg) and torque (0.1–0.2 Nm). Further tests were conducted for thermal properties (on differential scanning calorimetry set-up), mechanical properties (on ultimate tensile testing set-up, Shore D surface hardness, optical photomicrograph-based porosity analysis) and shape memory effect (with stimulus as water under different temperature conditions). The results of the study show that inducing 1% ZnO in PLA led to the formation of highly responsive composite with water as stimulus (at 25°C temperature), mechanically weak, porous, soft surface, while incorporation of 2% ZnO in PLA headed to less porous, harder and responsive composite to the water as stimulus (at 40°C temperature). The proposed combination of ZnO NPs and PLA shows encouraging range of crystallinity, tensile properties and shape memory effect, which made it an eligible candidate for 3D printing applications.